1993
DOI: 10.1037/h0079413
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of professional competence: Cross-disciplinary ratings of psychologists, social workers, and psychiatrists.

Abstract: Psychiatrists, psychologists, social workers, and nurses rated members of the first three disciplines on effectiveness of intervention for six hypothetical clients representing a range of mental health problems. Results revealed within-group bias, with perceptions that professionals sharing raters' own professional affiliation would be more helpful, expert, and warm, as well as the preferred recipient of referrals. Clinical social workers were rated highest on warmth by all raters but lowest on referral intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…This estimation is also supported by the findings of Koeske, Koeske and Mallinger's (1993) that psychologists and psychiatrists both gave social workers the highest ratings for warmth. The study participants indicated that their skills in listening, interviewing, developing rapport, and grasping non-verbal messages apparently contribute substantially to the resolution of the ethical dilemmas in hospitals.…”
Section: Role Definitionsupporting
confidence: 63%
“…This estimation is also supported by the findings of Koeske, Koeske and Mallinger's (1993) that psychologists and psychiatrists both gave social workers the highest ratings for warmth. The study participants indicated that their skills in listening, interviewing, developing rapport, and grasping non-verbal messages apparently contribute substantially to the resolution of the ethical dilemmas in hospitals.…”
Section: Role Definitionsupporting
confidence: 63%
“…The benefits of collaboration are usually assumed, while barriers to the full development of collaboration models are more frequently articulated. Obstacles include: lack of time, resources and commitment by organizations and the professions (Nandan, 1997); isolationism and inattention to collaboration within professional training and practice (Hilton, 1995); varying professional socialization processes that lead to competing perspectives on values or patient care issues (Mizrahi & Abramson, 1985); and, continuing competition for turf, status and autonomy (Koeske, Koeske & Mallinger, 1993;Ben-Sira and Szyf, 1992). The impact of managed care on collaborative relationships is yet unclear, although health providers, particularly physicians, have clearly experienced reduced autonomy in patient care decision making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, a focus on substitution of one provider for another threatens to increase the intensity of existing "turf wars" (Cummings 1990). When health professionals are asked about the type of provider most likely to provide the best level of service, they tend to favor their own profession (Koeske, Koeske, and Mallinger 1993). Although providers themselves often feel that their skills are sufficiently differentiated from other types of mental health workers, purchasers, and even clients, may be less aware of such distinctions (Murstein and Fontaine 1993).…”
mentioning
confidence: 99%